Climate change and armed conflict : hot and cold wars - Lee, James R., 1951- (Routledge studies in peace and conflict resolution., 2009)
This book examines the evolution of the relationship between climate change and conflict, and attempts to visualize future trends. Owing to the accumulation of greenhouse gases in the atmosphere, current trends in climate change will not appreciably alter over the next half century even if drastic action is taken now. Changes in climate will produce unique types and modes of conflict, redefine the value of important resources, and create new challenges to maintaining social order and stability. This book examines the consequences of climate change and argues that it has and will produce two ty.